Curriculum Evaluation Model: Paradigm and Implications in Improving the Quality of Education - Afriadi, Bambang; Fitri, Fitri (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study aims to analyse various models of curriculum evaluation and their implications for enhancing the quality of education, employing a comprehensive literature review approach. The curriculum is understood as an essential, planned framework in the educational process, influenced by diverse paradigms, including behavioristic, cognitive, constructivist, and humanistic, as well as the contributions of prominent educational thinkers such as Ralph W. Tyler, Benjamin Bloom, Jerome S. Bruner, and John Dewey. The results of the analysis show that curriculum evaluation models, including the Stufflebeam Context, Input, Process, Product (CIPP) Model, the Stake Responsive Model, and the Formative and Summative Evaluation classifications, offer a unique perspective in assessing the effectiveness of education. The CIPP model offers a comprehensive framework, spanning from planning to outcomes. The Responsive Stake Model highlights the importance of stakeholder perspectives and dynamic contexts, while Formative and Summative Evaluation function to facilitate continuous improvement and strategic decision-making. On the other hand, Tyler's Goal-Oriented Model emphasises accountability through the achievement of measurable targets. It is concluded that there is no single model that is superior for all situations; The selection of the model must be adaptive to the objective, context, and philosophy of the evaluation. This study recommends a multiparadigm approach and blended methods in curriculum evaluation to achieve a more comprehensive understanding, as well as encourage active stakeholder engagement and the utilisation of formative evaluations for continuous improvement. An in-depth understanding of these various models is crucial for educators and policymakers in designing relevant and high-quality education systems.